Identification of the Granule-Bound Starch Synthase (GBSS) Genes Involved in Amylose Biosynthesis in Tartary Buckwheat (Fagopyrum tataricum (L.) Gaertn.) - Juan Huang; Fei Liu; Jieqiong Zhang; Bin Tang; Jiao Deng; Taoxiong Shi; Liwei Zhu; Hongyou Li; Qingfu Chen (Plants)
Tartary buckwheat is a nutrient-rich pseudo-cereal whose starch contents, including amylose and amylopectin contents, and their properties hold significant importance for enhancing yield and quality. The granule-bound starch synthase (GBSS) is a key enzyme responsible for the synthesis of amylose, directly determining the amylose content and amylose-to-amylopectin ratio in crops. Although one has already been cloned, the GBSS genes at the genome-wide level have not yet been fully assessed and thoroughly analyzed in Tartary buckwheat. This study comprehensively analyzed the FtGBSSs in Tartary buckwheat. Based on the genome data of Tartary buckwheat, five FtGBSS genes, namely FtGBSS-1 to FtGBSS-5, were identified on three chromosomes, exhibiting about 1800 bp lengths in their CDSs and numerous exons and introns in gene structures. Amino acid analyses revealed high homology in ten GBSS proteins from Tartary buckwheat, rice, maize, and Arabidopsis thaliana, with a specific starch synthase catalytic domain and ten conserved motifs. The Tartary buckwheat GBSS proteins had a closer relationship with GBSS proteins from monocot based on evolutionary relationship analysis. Expression analyses suggested that the FtGBSS genes showed distinct tissue-specific expression patterns in Tartary buckwheat and rice-Tartary buckwheat. Among them, FtGBSS-1, FtGBSS-2, and FtGBSS-4 were higher expressed in the root, stem, or flower, suggesting that they have a role in the amylose synthesis of these tissues. Notably, FtGBSS-3 and FtGBSS-5 were more highly expressed in seeds than in other tissues, suggesting that they have a pivotal role in amylose synthesis of the seeds of Tartary buckwheat. Furthermore, the cis acting elements in the promoters of FtGBSSs and their binding transcription factors (TFs) were investigated. A protein–protein interaction network was constructed and co-expression was analyzed based on the gene expression patterns of the FtGBSSs, and the identified TFs, belonging to bZIP, ERF, bHLH, and MADS-box TF families, were identified within this network, and their expression patterns were significantly correlated to the expression patterns of two seed-specific FtGBSS genes (FtGBSS-3 and FtGBSS-5). Finally, FtGBSS1-5 was successfully transformed into rice through transgenic manipulation, and the FtGBSS1-5 overexpression lines showed an increase in amylose content accompanied by a reduction in amylopectin and total starch contents compared with WT. Overall, this research not only deepens our understanding of the molecular mechanisms of amylose synthesis in Tartary buckwheat, but also provides scientific insights for enhancing crop amylose content and quality through molecular breeding.